Sabbatical Leave Report - Inguanti, Joseph J. (2016)
A study that explores the role of images of the landscape in marketing America to would-be Italian emigrants in the era of the Great Migration (1880-1920).
Keywords: dept.art; faculty_collection; sabbatical_report

The convergence of critical pedagogy with arts-based service-learning - Alexander, Amanda; Schlemmer, Ross H (Convergence of Contemporary Art, Visual Culture, and Global Civic Engagement, 2016)
Neoliberal globalization and politics are reshaping the landscape in the United States and other countries; consequently, broader and more critical perspectives about education, community, and the arts are becoming increasingly more important. In the field of education, critical pedagogy has become a philosophy to expose, critique, and challenge neoliberal free market capitalism. Critical pedagogy becomes the link between local and global perspectives that reveals conditions of social and cultural injustices. Through socially engaged art education and service-learning initiatives, the authors have been engaging their students to become actively engaged citizens. This chapter offers a qualitative critique of the authors' own pedagogical practices through the convergence of critical pedagogy and arts-based service-learning by applying, adapting, and revising existing models of critical pedagogy such as Cipolle's (2010) “four elements of critical consciousness development” (p. 40) and Shor's (1992) methods for implementing critical pedagogy.
Keywords: dept.art

The Dutch Encounter with Italy - Levine, David A. (The Ashgate Research Companion to Dutch Art of the Seventeenth Century, 2016)
Keywords: dept.art